Preparation and In vitro Evaluation of Mucoadhesive Tablets of Montelukast Sodium - Bithi, Farzana Akter; Saha, Tushar; Ahmed, Nusrat; Hasan, Ikramul; Reza, Md Selim (Bangladesh Pharmaceutical Journal, 2018)
Mucoadhesive tablets of montelukast sodium were prepared in order to release the drug for a prolonged period of time so as to reduce the frequency of administration. Direct compression technique was applied using the mucoadhesive polymers which were Methocel K4M CR, Methocel K15M CR, Methocel K100M CR and Eudragit RLPO. Highest percent release of drug after 8 hours was 76% for Methocel K4M CR, 72.13% for Methocel K15M CR, 65.68% for Methocel K100M CR, 65.53% for the combination of Methocel K15M CR and Eudragit RLPO. Higuchi, Krosmeyer-Peppas was the best fitted model for drug release. The Methocel K15M CR containing drug showed good mucoadhesive strength. The highest ex-vivo mucoadhesive strength and ex-vivo residence time were observed with Methocel K15M CR and Eudragit RLPO combination. Fourier transform infrared (FT-IR) spectroscopy revealed the compatibility of drug with the polymers. Bangladesh Pharmaceutical Journal 20(2): 123-131, 2017